أثر التمويل المصرفي على القطاع الزراعي .2021 - دراسة تجربة المصرف الزراعي الليبي للفترة 1970: The impact of financing bank on agricultural sector An empirical study of Libyan Agriculture Bank during 1970- 2021 - يوسف يخلف مسعود, (Journal of North African Economies, 2025)
The study aimed to verify the effectiveness of loans granted by the Libyan Agricultural Bank in creating a boom in the income of agricultural activity, this study relied on a time period extending from 1970 to 2021, so it were used advanced econometric approaches. Thus, the study concluded that a long-term bank credit variable had a positive impact on the income of agricultural activity, and in the short term there is a strong relationship between an agricultural credit the income of agricultural activity variables, finally, the shock of the economic blockade is associated with an inverse relationship with the income of agricultural activity.